APLIKASI BACA BUKU UNTUK TUNANETRA LOW VISION MENGGUNAKAN OPTICAL CHARACTER RECOGNITION DAN TEXT TO SPEECH - Izzah, Fatimah Nurul; Supriyadi, Ujang (Journal of Mandalika Literature, 2023)
Based on data from the Ministry of Social Affairs for 2022, the total number of blind people is 11,368 and low vision is 6,818 with a total of 18,186 blind people in Indonesia. As many as 21.9% of the total number of persons with disabilities are persons with disabilities who are in the effective period of obtaining proper education. On the other hand, educational facilities and infrastructure are not fully friendly to persons with disabilities. The Center for Development and Empowerment of Kindergarten and Special Education Educators and Education Personnel (PPPPTK and PLB), which is under the Ministry of Education and Culture, Research and Technology, recommends the use of assistive devices to help students who have visual impairments. Responding to these challenges, this application was developed to help read books or print media. The results of testing this application are easy to use because it has a simple appearance and there is an audio guide. It was found that the development of this innovative product is a user-friendly assistive application for the blind with the main features of Audio Guide Assistance, Auto Capture, Image to Speech, Audio book and Multiple Audio-page Grouping.